Innovative hybrid technique of bile duct exploration in the treatment of Choledocolithiasis - Navarini, Daniel; de Albuquerque, Henrique Waltrick; Albuquerque, Antônio Benincá; Rovani, André Luca Boeira; Dessanti, Deise; Reffatti, Diego; Madalosso, Carlos Augusto Scussel (Clinical and Biomedical Research, 2020)
Common bile stone disease (CBDS) is frequent and has potentially severe complications, such as acute biliary pancreatitis and cholangitis. Unnecessary and unplanned procedures must be avoided, so before choosing the best treatment of common bile duct lithiasis it is essential to have a proper diagnose. CBDS is currently treated by therapeutic endoscopic retrograde cholangiopancreatography (ERCP) or laparoscopic bile duct exploration (LCBDE). The aim of this article is to present a innovative hybrid technique of common bile duct exploration, on account of one option in those cases where the laparoscopic approach is not resolutive, avoiding the need of conversion to open approach technique. The hybrid technique has the same benefits of open and laparoscopic techniques, but without increasing costs with material and with good resolutivity in complex cases of common bile duct stones. Keywords: Choledocholithiasis; laparoscopic common bile duct exploration; LCBDE; open common bile duct exploration